(3GdeUfas - (3CHh HcQ YHO Gddg Hf eMeO Hf CHj TjHI GdYHSj, GHf CHj TjHI,J (B235 (3g` s
(3ChdgG (B:s
(3GdhVhA s
(3BNQgG (B:s
(3Chd GdUdGI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B117s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B103 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1711s
(3eUOQ GbJfGA GdCUd (B:s
(3eQGO edG (B(1/ 588) s
Keywords: (3GdMOjK h GdeUWdMs